UNIVERSITY STUDENTS’ PERCEPTIONS TOWARD AN ONLINE INTERACTIVE ENGLISH LEARNING PLATFORM WITH A SERIES OF GRADED E-READERS - Sung, Dylan (Proceedings of the International Conference on Education, 2019)
In recent times, the Ministry of Education in Taiwan has been urging universities to make the most of online learning. The purpose of this study was to investigate Taiwanese university students’ perceptions and feedbacks regarding an online interactive English learning platform with a series of graded e-readers. The target population chosen for this study was the students at a selected university in northern Taiwan. A survey questionnaire was designed to collect data for this study. Results found that when the user interface is not intuitive and the experience is not smooth, students hold a fairly negative attitude toward the use of the online platform. Quality of the learning content can easily be overlooked if the users are not readily provided with easy navigation through the platform. The platform’s lack of functionality for users to improve speaking skills is indicated as a major weakness. Furthermore, standardizing the use of an online English learning platform, as a mandatory portion of an English course, can lead to adverse results. It is recommended that universities should thoroughly assess students’ feedback and learning outcomes before computer technology is mandatorily incorporated into the syllabus of an English course.